Os romances juvenis de Álvaro Magalhães - Nogueira, Carlos (2016)
With his works translated in countries such as Spain, France and Brazil, Álvaro Magalhães is not only one of the great writers of Portuguese and Lusophone juvenile fiction, but also one of the most prominent names in European and world literature. Through the various thematic and narrative resources that he employs in the creation of a unique language, among the multiple and unusual senses of serious and humorous, among the elements of various domains of knowledge and universal culture that he invokes and contrasts, this author has a unique place in universe of novels aimed primarily at young readers.